Machining of pure molybdenum using WEDM. (15th October 2020) - Mouralova, K.; Benes, L.; Prokes, T.; Bednar, J.; Zahradnicek, R.; Fries, J.
Highlights: Wire electrical discharge machining of pure molybdenum. Optimum setting of machine parameters was found by using design of experiment. Influence of cut orientation through semi-finished product was tested. Abstract: Wire electrical discharge machining (WEDM) is an unconventional technology that is indispensable in almost all industries as well as pure molybdenum, which is used in almost all areas of industry, from energy through chemical, automotive, metallurgical to physical laboratory equipment designed for vacuum. However, due to its energy demands, the effort is to maximize the cutting speed with an emphasis on maintaining the quality of machined surfaces, which also often contain a number of defects in the form of cracks or burnt cavities. For this reason, the aim of this study was to find the optimum setting of the machine parameters using a design of experiment consisting of 33 rounds, with the material of pure molybdenum being examined. An extensive analysis of all machined samples was performed in terms of defects occurrence in the surface and subsurface layers, the analysis of topography and morphology including 3D surface reliefs, the analysis of chemical composition with dependence on diffusion processes and measurement of residual stress in the workpieces. Due to the high occurrence of cracks, the influence of the cut orientation through the semi-finished product was tested, and its fundamental influence on the occurrence of massive cracks was found out. In addition, to minimize the topography parameters and maximize the cutting speed, the machine parameters were set to: gap voltage = 70 V, pulse on time = 6 µs, pulse off time = 30 µs, wire speed 10 m·min −1 and discharge current = 35 A.